Simulation of Coated Particles Breakage Using a low Fidelity DEM–BPM Model - Safdar, Wasif; Heinrich, Stefan; Düster, Alexander (Proceedings in applied mathematics and mechanics, 2025)
ABSTRACT Previous studies have demonstrated that filling a ship's double hull cavity with lightweight glass particles, like Poraver significantly enhances its ability to withstand collisions. The energy absorption capability of such particles can be improved by coating them in a fluidised spray granulation process. In order to find the extent of this improvement, a numerical model needs to be developed. For that purpose, the discrete element method (DEM) with the bonded particle method (BPM) is employed using the open‐source code MUSEN. This allows the breakage of particles to be simulated using a cluster of particles bonded to each other. Since a single particle in the experiment is represented with an agglomerate of several smaller particles in the simulation, it significantly adds to the computational costs and limits the scale of the simulations which can be performed. This paper explores the different fidelities of a DEM–BPM numerical model with its advantages and disadvantages in its depiction of a coated particle breakage.